PENGARUH PEMBERIAN AMPAS SAGU TERHADAP PERSENTASE KARKAS AYAM BROILER - Mulyani Puji Rahayu; A. Tenny Damayanti Indriastuti; Henny V Saiya (Faculty of Agriculture, Musamus University, 2019)
Sago waste is a by-product of sago palm processing. It is rich of carbohidrate and other organic materials. Sago waste high potensial as animal feed.The aims of this research were to determine of effect sago waste to carcass percentage. The experiment was run in completely randomized design wich consisted of 4 feed treatments and 3 replications. The result showed that all variables observed were affected by percentage of sago waste (0%, 5%, 10%, and 15%). The good carcass percentage and cooking loss were found in 5 % treatments. Key Words : sago waste; chicken meat; carcass persentage;karkas